2013
DOI: 10.1007/s00018-013-1520-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of recombination between diverged sequences in a mammalian genome by a double-strand break

Abstract: To investigate whether mammalian cells can carry out recombinational double-strand break (DSB) repair between highly diverged sequences, mouse fibroblasts were transfected with DNA substrates that contained a "recipient" thymidine kinase (tk) gene disrupted by the recognition site for endonuclease I-SceI. Substrates also contained a linked "donor" tk gene sequence. Following DSB induction by I-SceI, selection for tk-expressing clones allowed recovery of repair events occurring by nonhomologous end-joining or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…When DNA recombination happens between imperfectly matching sequences (synonymous with diverged sequences and homeologous sequences), the restored DNA molecule would have certain DNA sequence replaced by that of the DNA template. These recombination events with a homeologous conversion tract are thus called homeologous recombination events (HeR events) (53)(54)(55)(56). Due to HeR's deleterious consequences to gene function and genome stability, a lot of research have been done to address the mechanism how cells avoid DNA recombination between diverged sequences.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…When DNA recombination happens between imperfectly matching sequences (synonymous with diverged sequences and homeologous sequences), the restored DNA molecule would have certain DNA sequence replaced by that of the DNA template. These recombination events with a homeologous conversion tract are thus called homeologous recombination events (HeR events) (53)(54)(55)(56). Due to HeR's deleterious consequences to gene function and genome stability, a lot of research have been done to address the mechanism how cells avoid DNA recombination between diverged sequences.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Pursuing the previous findings in our laboratory (53,55), a systematic research has been done to explore the mechanism how mammalian cells exclude highly diverged sequences from DNA recombination, and the results are presented in current dissertation.…”
Section: List Of Tablesmentioning
confidence: 99%
“…AW91 is composed of 20 nucleotides from the noncoding strand of the neomycin gene mapping 25 through 44 bp downstream from the neomycin start codon, with an Sp6 primer appended to the 5' end of the primer. PCR was carried out using Ready-To-Go PCR beads (GE Healthcare) and a "touchdown" PCR protocol as previously described (17). PCR products were expected to be ∼1.4 kb in length unless detectable deletions or insertions had occurred.…”
Section: Pcr Amplification and Dna Sequence Analysismentioning
confidence: 99%
“…We also reported that when a spontaneous recombination event occurs within highly homologous sequences, mammalian cells fastidiously exclude adjoining mismatched bases from gene conversion tracts (15). Recently, we observed that the exclusion of mismatches from gene conversion events initiated within high homology is somewhat relaxed when the mismatches are positioned close to the DSB initiating the HR event (17). Nonetheless, the need for a stretch of high homology for the initiation of HR remains intact in proximity to a DSB (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation